Cognition-Modulated Frontal Activity in Prediction and Augmentation of Antidepressant Efficacy: A Randomized Controlled Pilot Study. (27th August 2014) - Li, Cheng-Ta; Hsieh, Jen-Chuen; Huang, Hsiang-Hsuan; Chen, Mu-Hong; Juan, Chi-Hung; Tu, Pei-Chi; Lee, Ying-Chiao; Wang, Shyh-Jen; Cheng, Chih-Ming; Su, Tung-Ping
Abstract: Higher rostral anterior cingulate cortex (rACC) activity correlated with frontal theta power (frontalθ) is associated with better antidepressant responses. The antidepressant efficacy of repetitive transcranial magnetic stimulation (rTMS) varied widely; however, the effects of TMS might be modulated by manipulating the pretreatment neural states. Therefore, we conducted a pilot study to investigate whether manipulated frontalθ before rTMS treatment could predict and augment antidepressant responses. A computerized rACC-engaging cognitive task (RECT) was exploited continuously for 10 min to patients with major depressive disorder. In total, 36 patients were randomized to 3 groups (Group-A: RECT[active] + rTMS[active]; Group-B: RECT[sham] + rTMS[active]; Group-C: RECT[active] + rTMS[sham]). Frontalθ and whole-brain glucose uptakes were assessed. We found that the RECT-modulated increases in frontalθ correlated well with rACC glucose uptakes. The treatment responders demonstrated a significant increase in frontalθ after RECT. Post-RECT frontalθ had good sensitivity/specificity in predicting antidepressant responses to rTMS. Group-A had more reduction in total depression scores, had more responders, and was more likely to achieve remission than other groups (Group-A [41.6%] > Group-B [16.6%] > Group-C [0%], P < 0.05). A significant enhancement in the post-1st-rTMS frontalθ was observed in Group-A responders but not in Group-B responders, supporting the argument that RECT-modulated rTMS augmented rTMS efficacy. In conclusion, this study suggests that manipulating pre-rTMS neural activity could predict and augment antidepressant effects to rTMS treatment.